Life after oral English certification: The consequences of the Test of Oral English Proficiency for Academic Staff for EMI lecturers. (April 2017) - Dimova, Slobodanka
Abstract: Internationalization of higher education has resulted in rapid developments of English-medium instruction (EMI) courses in non-Anglophone countries in Europe and Asia. Due to the growing concerns about lecturers' ability to teach in English, several European universities have implemented policies for internal assessment of lecturers' English proficiency to ensure the quality of teaching in EMI programs. However, research on the measured construct and the reliability and the validity of these assessments remains scarce. Based on interviews with tested university lecturers and formative feedback analysis, this study discusses the consequences resulting from score and feedback interpretations and uses as part of the validation process of TOEPAS (Test of Oral English Proficiency for Academic Staff), which is a performance-based test used for oral English certification of lecturers at the University of Copenhagen. The results suggest convergence of intended and actual uses of TOEPAS results, though the alignment of the expected outcomes and the actual consequences was not complete, especially in relation to the uses of the formative feedback. The implications of these findings point to the need for a distributed stakeholder responsibilities regarding result communication, decision-making, and learning. Highlights: Consequences of oral English proficiency tests for EMI lecturer certification investigated. Instrumental case study based on EMI lecturer interviews and written feedback data. Written feedback on oral test performance overly technical for EMI lecturers. More adverse personal and professional test impact for certain EMI lecturer subgroups. Need for alignment of EMI certification with internationally recognized assessment scales.